Analysis of Flexitank Heating Pad Data Temperature Using Labview - Mohd Zahari, Siti Norsyaheeza; Mohd Shah, Nor Shahida; Sadun, Amirul Syafiq; Lurdsuami, Sharon (Progress in Engineering Application and Technology, 2022)
The heater pads are made to allow steam that has a low melting point and easily solidify when subjected to low temperatures, to be released using steam as a heating source. This study focuses on analysing the temperature data and obtaining the mean, maximum and minimum values, standard deviation, and observing whether the temperature value is out of range of the required temperature so that we can improve the heating pad of the Flexitank by taking necessary actions to maintain the condition of the heating pad. This project uses NI LabVIEW as a platform to analyse the raw data from MS Excel CSV files. Graphical User Interface (GUI) was developed on LabVIEW to let the user operate the system. There is no complete data for the heating pad of the Flexitank due to the leakage at the flow tube. Thus, the data used for this analysis system is the temperature data obtained from the thermocouple sensor only in the input point. However, the analysis system can be used for future work.